A current collector with functional coating and preparation method and application thereof

By adopting two adhesive systems and corona treatment methods, the adhesiveness and electron conductivity of the functional coating and the metal current collector are improved, the problems of insufficient adhesiveness and high gas production in the prior art are solved, and the cycle life and performance of the energy storage device are significantly improved.

CN119481084BActive Publication Date: 2025-04-01TIANJIN PLANNANO ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510065516.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-01
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The existing functional coatings are insufficiently adhesive in energy storage devices, resulting in poor mechanical strength and cycle life of the electrode itself and a large amount of gas production.

Method used

Two adhesive systems are adopted. The first adhesive has a good bonding effect with the metal current collector after corona treatment, and the second adhesive has an excellent bonding effect with the active layer. The two cooperate with each other to improve the bonding performance of the functional coating, and reduce side reactions caused by functional groups through cross-linking reactions.

Benefits of technology

The electron conduction between the electrode active substance and the current collector is significantly enhanced, the current distribution consistency of the electrode sheet is improved, the cycle life of the energy storage device is improved, and gas production is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481084B_ABST
    Figure CN119481084B_ABST
Patent Text Reader

Abstract

The present invention relates to a current collector with a functional coating, a preparation method and an application thereof, and relates to the fields of lithium-ion battery technology and supercapacitor technology; the present invention comprises the following steps: (1) uniformly mixing a conductive agent, a first binder and pure water for the first time to obtain a first mixed slurry; adding a second binder to the first mixed slurry, and uniformly mixing for the second time to obtain a second mixed slurry; adjusting the slurry viscosity of the second mixed slurry to less than 1000 Pa·s to obtain a functional coating slurry; (2) applying the functional coating slurry to at least one side of a metal current collector after corona treatment, and drying to obtain a current collector with a functional coating. The present invention effectively enhances the electronic conduction between the electrode active material and the current collector, improves the current distribution consistency of the electrode plate, and increases the cycle life of the energy storage device; the present invention has simple equipment, simple operation process, effectively reduces the labor intensity of workers, and is suitable for promotion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of lithium ion battery technology and supercapacitor technology, and in particular to a current collector with a functional coating, a preparation method thereof and an application thereof. Background Art

[0002] Battery or capacitor pole piece is one of the components of the energy storage unit monomer, and their performance directly determines the performance of the energy storage device. In conventional batteries or double-layer capacitors, some monomers use functional coatings to improve performance; for the dry process of batteries and supercapacitors currently under development, functional coatings are an indispensable and important part of pole pieces and play a vital role in the performance of pole pieces. The main functions of functional coatings include connecting the active layer and the current collector as an adhesive layer, maintaining the integrity and stability of the entire electrode, and providing an efficient conductive channel so that electrons can be quickly and efficiently transmitted between the current collector and the active layer / self-supporting film. Therefore, the long cycle stability and high electron transport capacity of the functional coating are the two key indicators for evaluating its performance. However, the material system design and process formulation optimization of existing functional coatings face many technical difficulties. In terms of adhesion, the functional coating must not only be stably bonded to the surface of the metal current collector, but also ensure good bonding with the inorganic active material layer components, and need to withstand high temperature, high pressure and corrosion of organic electrolytes, etc. These are all factors to be considered when selecting functional coating binders. At the same time, the morphology, particle size, intrinsic conductivity of the conductive agent and its binding properties with the above-mentioned binder also affect the conductivity and mechanical properties of the functional coating.

[0003] At present, high-performance supercapacitors and other energy storage devices still mainly use expensive imported metal foils that have been treated with surface corrosion. This type of corroded foil uses deep surface corrosion to increase its surface roughness and specific surface area, thereby improving the contact interface and providing more strong bonding sites. At the same time, during the wet coating process, the binder and activated carbon material penetrate into the pores with the solvent to enhance their mechanical connection, ensuring strong bonding between the active material layer and the current collector. However, this type of current collector is expensive, and for ordinary smooth metal foils with significantly lower costs, when using the same functional coating system, the bonding strength with the active layer is relatively low due to insufficient surface contact sites. In view of the above technical difficulties, in order to make up for the deficiencies in the current primer foil preparation process technology, the present invention provides a current collector with a functional coating, a preparation method and an application thereof. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a current collector with a functional coating and a preparation method and application thereof, with the purpose of increasing the bonding force between the functional coating and the metal current collector and the mechanical strength of the electrode itself, significantly reducing the gas generation of the energy storage device, and improving the cycle life of the device.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] In a first aspect, a method for preparing a current collector having a functional coating comprises the following steps:

[0007] (1) uniformly mixing the conductive agent, the first binder and pure water for the first time to obtain a first mixed slurry;

[0008] Adding a second binder to the first mixed slurry, mixing for a second time to obtain a second mixed slurry; adjusting the slurry viscosity of the second mixed slurry to less than 1000 Pa·s to obtain a functional coating slurry;

[0009] (2) Applying the functional coating slurry to at least one side of a corona-treated metal current collector, and drying the slurry to obtain a current collector having a functional coating.

[0010] The present invention uses two adhesive systems. On the one hand, the first adhesive has good bonding effect with the metal current collector after corona treatment, and the second adhesive has excellent bonding effect with the active layer. The two cooperate with each other to improve the bonding function of the functional coating and different objects. On the other hand, during the high-temperature baking stage, the functional groups carried by the first and second adhesives can undergo cross-linking reactions with each other, thereby reducing the content of excess functional groups and reducing the side reactions with the organic electrolyte caused by the functional groups.

[0011] The beneficial effects of the present invention are as follows: the present invention effectively enhances the electronic conduction between the electrode active material and the current collector, improves the current distribution consistency of the electrode pole piece, and increases the cycle life of the energy storage device; the present invention has simple equipment and a simple operation process, which effectively reduces the labor intensity of workers and is suitable for promotion; the method of the present invention has a simple and fast process, is easy to operate, has low requirements on equipment during the production process, and is convenient for actual production operations; the processing method of the present invention does not require any organic solvents, and can reduce the emission and pollution of chemical products.

[0012] Based on the above technical solution, the present invention can also be improved as follows.

[0013] Furthermore, the metal current collector includes copper foil or aluminum foil.

[0014] Further, the conductive agent includes at least one of metal powder, acetylene black, Ketjen black, furnace black, conductive carbon black (SP), conductive graphite, carbon nanotubes, carbon fibers, and graphene;

[0015] The first binder includes at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), and styrene-butadiene rubber latex (SBR);

[0016] The second binder includes at least one of an acetamide-based binder, starch, polyacrylonitrile (PAN), polyacrylate, and polyacrylic acid (PAA).

[0017] The beneficial effect of adopting the above further scheme is that the first and second adhesives cooperate with each other to improve the bonding performance of the functional coating, and at the same time the two adhesives consume each other's excess functional groups, reducing the gas production side reaction caused by the functional groups.

[0018] Further, the weight ratio of the conductive agent, the first binder and the pure water is 2:1:97-20:10:70;

[0019] The second binder accounts for 30% to 70% of the weight of the first binder;

[0020] The parameters for the first mixing in step (1) are: a stirring blade linear speed of 4 m / s to 15 m / s, and a mixing time of 30 min to 120 min;

[0021] The parameters for the second mixing in step (1) are: a stirring paddle linear speed of 4 m / s to 15 m / s, and a mixing time of 30 min to 120 min.

[0022] The beneficial effect of adopting the above further solution is that by adjusting the stirring parameters, the molecular chains of the binder are fully unfolded, the branches are entangled with each other, and the mixing is more uniform.

[0023] Furthermore, step (1) further includes: adding a metal chelating agent to the second mixed slurry, mixing evenly for a third time, and obtaining a third mixed slurry; and adjusting the slurry viscosity of the third mixed slurry to less than 1000 Pa·s, and obtaining a functional coating slurry.

[0024] The beneficial effect of adopting the above further solution is: by adopting a mixed binder system (second mixed slurry) and supplementing it with a metal chelating agent, the affinity and adhesion between the binder and the surface of the metal current collector are further enhanced.

[0025] Further, the metal chelating agent includes at least one of sodium carbonate, sodium orthophosphate, ethylenediaminetetraacetic acid (EDTA), disodium ethylenediaminetetraacetic acid (EDTA-2Na), tetrasodium ethylenediaminetetraacetic acid (EDTA-4Na), disodium nitrilotriacetate (NTA), citric acid (CA), tartaric acid (TA) and gluconic acid (GA);

[0026] The metal chelating agent accounts for 2% to 10% of the total weight of the first binder and the second binder;

[0027] The parameters for the third mixing are: stirring paddle linear speed 4m / s~15m / s, mixing time 30min~120min.

[0028] The beneficial effect of adopting the above further solution is that the polycondensation and agglomeration of the polymer binder can be reduced through appropriate stirring parameters.

[0029] Furthermore, the coating method of the functional coating slurry in step (2) includes gravure coating; the shape of the gravure roller surface used in the gravure coating includes at least one of a slash straight line, a diamond quadrilateral, a square, and a honeycomb hexagon; the parameters of the gravure coating are: the mesh number of the gravure roller is 50-300 meshes, the coating speed is 4m / min-60m / min, and the coating thickness is 1μm-12μm;

[0030] The drying parameters in step (2) are: drying temperature is 50°C to 180°C, and the drying time is 0.5min to 10min.

[0031] The beneficial effect of adopting the above further scheme is that the functional grid conductive coating designed by the present invention obtains more excellent interface contact performance, can obtain better adhesion performance and charge transfer performance, makes the electron conduction between the electrode active material and the electrode current collector more uniform, can improve the current distribution consistency of the electrode pole piece, and collects local microcurrent.

[0032] Furthermore, the specific parameters of the corona treatment of the metal current collector in step (2) are: voltage 380 V, corona power 2 kW to 8 kW, current 6 A to 15 A, and corona speed 4 m / min to 60 m / min.

[0033] The beneficial effect of adopting the above further scheme is that the impurities such as oil stains on the surface of the current collector can be effectively reduced by corona treatment, while constructing bonding active points to improve the bonding performance.

[0034] In a second aspect, a current collector with a functional coating is provided, wherein the current collector with a functional coating is prepared by the preparation method.

[0035] The beneficial effect of adopting the above scheme is that the current collector adopting the above scheme can improve the conductivity and bonding stability of the pole piece, reduce the pole piece resistance of the energy storage device, and extend the service life.

[0036] A third aspect provides an application of a current collector having a functional coating, wherein the current collector having a functional coating is used to prepare an energy storage device.

[0037] The beneficial effect of adopting the above scheme is that the energy storage device prepared by using the electrode with functional coating has better electron transmission capability and lower resistance than the conventional energy storage device, and at the same time has better cycle stability, less gas production and higher safety factor.

[0038] Furthermore, the energy storage device includes a lithium-ion battery or a supercapacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 For comparison of bonding effects; wherein (a) is the unmodified current collector of Example 1, and (b) is the surface-modified current collector of Example 2;

[0040] Figure 2 The internal pressure test results of the supercapacitors of Examples 1-4;

[0041] Figure 3 The effects of different conductive coating forms on the conductivity of the pole piece under the same load in Examples 1-4;

[0042] Figure 4 The cycle performance of Examples 1-4. DETAILED DESCRIPTION

[0043] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0044] This embodiment relates to a method for preparing a current collector having a functional coating, comprising the following steps:

[0045] (1) uniformly mixing the conductive agent, the first binder and pure water for the first time to obtain a first mixed slurry;

[0046] Adding a second binder to the first mixed slurry, mixing for a second time to obtain a second mixed slurry; adjusting the slurry viscosity of the second mixed slurry to less than 1000 Pa·s to obtain a functional coating slurry;

[0047] (2) Applying the functional coating slurry to at least one side of a corona-treated metal current collector, and drying the slurry to obtain a current collector having a functional coating.

[0048] The present invention effectively enhances the electron conduction between the electrode active material and the current collector, improves the current distribution consistency of the electrode pole piece, and increases the cycle life of the energy storage device; the present invention has simple equipment and a simple operation process, effectively reduces the labor intensity of workers, and is suitable for promotion; the method of the present invention has a simple and fast process, is easy to operate, has low requirements on equipment during the production process, and is convenient for actual production operations; the processing method of the present invention does not require any organic solvents, and can reduce the emission and pollution of chemical products.

[0049] Preferably, in this embodiment, the metal current collector includes copper foil or aluminum foil.

[0050] In this embodiment, the conductive agent preferably includes at least one of metal powder, acetylene black, Ketjen black, furnace black, conductive carbon black (SP), conductive graphite, carbon nanotubes, carbon fibers, and graphene;

[0051] The first binder includes at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), and styrene-butadiene rubber latex (SBR);

[0052] The second binder includes at least one of an acetamide-based binder, starch, polyacrylonitrile (PAN), polyacrylate, and polyacrylic acid (PAA).

[0053] Preferably, in this embodiment, the weight ratio of the conductive agent, the first binder and the pure water is 2:1:97-20:10:70; specifically, it can be 20:5:5:70, 15:7:78, etc.;

[0054] The second binder accounts for 30% to 70% of the weight of the first binder, and specifically may be 30%, 40%, 50%, 60%, 70%, etc.;

[0055] The parameters for the first mixing in step (1) are: a stirring paddle linear speed of 4 m / s to 15 m / s, specifically 5 m / s, 8 m / s, 10 m / s, 12 m / s, 14 m / s, etc., and a mixing time of 30 min to 120 min, specifically 40 min, 60 min, 80 min, 90 min, 120 min, etc.;

[0056] The parameters for the second mixing in step (1) are: a stirring paddle linear speed of 4 m / s to 15 m / s, specifically 5 m / s, 8 m / s, 10 m / s, 12 m / s, 14 m / s, etc., and a mixing time of 30 min to 120 min, specifically 40 min, 60 min, 80 min, 90 min, 120 min, etc.

[0057] In this embodiment, step (1) further includes: adding a metal chelating agent to the second mixed slurry, mixing for a third time to obtain a third mixed slurry; adjusting the slurry viscosity of the third mixed slurry to less than 1000 Pa·s to obtain a functional coating slurry. By using a mixed binder system (second mixed slurry) supplemented with a metal chelating agent, the affinity and adhesion between the binder and the surface of the metal current collector are further enhanced.

[0058] In this embodiment, the metal chelating agent preferably includes at least one of sodium carbonate, sodium orthophosphate, ethylenediaminetetraacetic acid (EDTA), disodium ethylenediaminetetraacetic acid (EDTA-2Na), tetrasodium ethylenediaminetetraacetic acid (EDTA-4Na), disodium nitrilotriacetate (NTA), citric acid (CA), tartaric acid (TA) and gluconic acid (GA);

[0059] The metal chelating agent accounts for 2% to 10% of the total weight of the first binder and the second binder, and can specifically be 2%, 5%, 8%, 10%, etc.;

[0060] The parameters for the third mixing are: stirring paddle linear speed 4m / s~15m / s, specifically 5m / s, 8m / s, 10m / s, 12m / s, 14m / s, etc., mixing time 30min~120min, specifically 40min, 60min, 80min, 90min, 120min, etc.

[0061] In this embodiment, the coating method of the functional coating slurry in step (2) includes gravure coating; the shape of the gravure roller surface used in the gravure coating includes at least one of a slanted straight line, a rhombus quadrilateral, a square, and a honeycomb hexagon; the parameters of the gravure coating are: the mesh number of the gravure roller is 50-300 mesh, specifically 50 mesh, 100 mesh, 200 mesh, 300 mesh, etc.; the coating speed is 4m / min-60m / min, specifically 4m / min, 10m / min, 20m / min, 30m / min, 40m / min, 50m / min, 60m / min, etc.; the coating thickness is 1μm-12μm, specifically 2μm, 4μm, 6μm, 8μm, 10μm, etc.;

[0062] The parameters of drying in step (2) are: drying temperature is 50°C~180°C, specifically 50°C, 70°C, 80°C, 100°C, 150°C, 180°C, etc.; time is 0.5min~10min, specifically 1min, 2min, 5min, 7min, 9min, etc.

[0063] The functional grid conductive coating designed in the present invention obtains more excellent interface contact performance, can obtain better adhesion performance and charge transfer performance, makes the electron conduction between the electrode active material and the electrode current collector more uniform, can improve the current distribution consistency of the electrode pole piece, and collects local microcurrent.

[0064] Preferably, in the present embodiment, the specific parameters of the corona treatment of the metal current collector in step (2) are: voltage 380 V, corona power 2 kW to 8 kW, specifically 3 kW, 5 kW, 6 kW, etc.; current 6 A to 15 A, specifically 7 A, 8 A, 10 A, 13 A, etc.; corona speed 4 m / min to 60 m / min, specifically 4 m / min, 10 m / min, 20 m / min, 30 m / min, 40 m / min, 50 m / min, 60 m / min, etc.

[0065] This embodiment also relates to a current collector with a functional coating, and the current collector with a functional coating is prepared by the preparation method.

[0066] This embodiment also relates to an application of a current collector with a functional coating, and the current collector with a functional coating is used to prepare an energy storage device.

[0067] Preferably, in this embodiment, the energy storage device includes a lithium-ion battery or a supercapacitor.

[0068] In summary, the present invention introduces functional groups on the surface of the metal foil by electrochemically treating the surface of the metal foil to provide bonding sites and bonding force; then a mixed binder system is used together with a metal chelating agent to enhance the affinity and bonding between the binder and the surface of the light foil; in the drying process of the mixed binder system, excess hydroxyl and carboxyl functional groups will undergo a cross-linking reaction, which not only increases the bonding force between the functional coating and the current collector and the mechanical strength of the electrode itself, but also significantly reduces the gas production of the organic electrolyte, further improving the cycle life of the device. The present invention also found that printing a unique grid-like conductive coating can obtain better bonding and charge transfer properties, making the electronic conduction between the electrode active material and the electrode current collector more uniform, which can improve the current distribution consistency of the electrode pole piece and collect local microcurrents. The following is a detailed description with specific embodiments.

[0069] Embodiment 1:

[0070] This embodiment relates to a method for preparing a current collector having a common primer layer, comprising the following steps:

[0071] Step 1: Add the conductive agent SP, the binder PVDF and pure water in a mass ratio of 10:5:85 into a mixer, mix for 30 min, and stir at a paddle speed of 8 m / s to obtain a mixed slurry;

[0072] Step 2: adjusting the slurry viscosity of the mixed slurry to 200 Pa·s to obtain a common conventional coating slurry;

[0073] Step 3: Use a gravure coater to coat the ordinary conventional coating slurry on the A side and the B side of the metal aluminum foil. Before coating, the metal aluminum foil is not subjected to a corona device (specific parameters of the corona treatment are: voltage 380V, corona power 6kw, current 11A, and corona speed 12m / min), but is only subjected to coating and then immediately enters an oven; a gravure roller with a mesh count of 200 meshes and a straight line type is used, a coating speed of 8m / min, and a drying temperature of 100°C is used; and the base coated foil for a lithium battery or supercapacitor electrode is obtained by winding the foil;

[0074] Step 4: The dry supercapacitor film is composited on both sides of the primer foil by high-temperature roller pressing to prepare a capacitor electrode. The composite temperature is 150°C and the composite speed is 10m / min. Then it is assembled with a diaphragm (NKK TF 4030) and an electrolyte (DLC 3702) into a 3000F supercapacitor monomer as implementation example 1 and tested.

[0075] Embodiment 2:

[0076] This embodiment relates to a method for preparing a current collector having a coating, comprising the following steps:

[0077] Step 1: Add the conductive agent SP, the binder PVDF and pure water into a mixer in a mass ratio of 10:5:85, mix for 60 min, and stir at a paddle speed of 9 m / s to obtain a mixed slurry;

[0078] Step 2: adjusting the slurry viscosity of the mixed slurry to 500 Pa·s to obtain a functional coating slurry;

[0079] Step 3: Use a gravure coater to coat the functional coating slurry onto the A and B surfaces of the metal aluminum foil. Before coating, the metal aluminum foil passes through a corona device (specific parameters of the corona treatment are: voltage 380V, corona power 6kw, current 11A, and corona speed 12m / min). After the corona is finished, it is immediately coated and enters an oven; a gravure roller with a mesh count of 200 oblique lines is used, a coating speed of 15m / min, and a drying temperature of 100°C is used; and the base coated foil for lithium batteries or supercapacitor electrodes can be obtained by winding.

[0080] Step 4: The dry supercapacitor film was composited on both sides of the primer foil by high-temperature roller pressing to prepare a capacitor electrode. The composite temperature was 150°C and the composite speed was 10 m / min. Then, it was assembled with a diaphragm (NKK TF 4030) and an electrolyte (DLC 3702) into a 3000F supercapacitor monomer as implementation example 2 and tested.

[0081] Embodiment three:

[0082] This embodiment relates to a method for preparing a current collector having a functional coating, comprising the following steps:

[0083] Step 1: Add the conductive agent SP, the first binder carboxymethyl cellulose (CMC), styrene-butadiene rubber emulsion (SBR) and pure water in a mass ratio of 20:5:5:70 into a mixer, mix for 50 min, and set the stirring blade linear speed at 12 m / s to obtain a first mixed slurry;

[0084] Step 2: Adding the second binder polyacrylonitrile (PAN) to the first mixed slurry at a weight ratio of 50 wt% of the weight of the first binder, and continuing to mix using a mixer for 60 min at a stirring blade linear speed of 12 m / s to obtain a second mixed slurry;

[0085] Step 3: adding a metal chelating agent ethylenediaminetetraacetic acid (EDTA) to the second mixed slurry at 5% of the total amount of all binders (the first binder and the second binder), and continuing to mix using a mixer, with a mixing time of 60 min and a stirring paddle linear speed of 10 m / s to obtain a third mixed slurry;

[0086] Step 4: adjusting the slurry viscosity of the third mixed slurry to 400 Pa·s to obtain a functional coating slurry;

[0087] Step 5: Use a gravure coater to coat the functional coating slurry onto the A and B surfaces of the metal aluminum foil. Before coating, the metal aluminum foil passes through a corona device (specific parameters of the corona treatment are: voltage 380V, corona power 6kw, current 13A, and corona speed 14m / min). After the corona is finished, it is immediately coated and enters an oven; a gravure roller with a mesh count of 100 meshes and a straight line type is used, a coating speed of 30 m / min, and a drying temperature of 120°C is used; and the base coated foil for lithium battery or supercapacitor electrode is obtained by winding.

[0088] Step 6: The dry supercapacitor film is composited on both sides of the primer foil by high-temperature roller pressing to prepare a capacitor electrode. The composite temperature is 150°C and the composite speed is 10m / min. Then it is assembled with a diaphragm (NKK TF 4030) and an electrolyte (DLC 3702) into a 3000F supercapacitor monomer as implementation example 3 and tested.

[0089] Embodiment 4:

[0090] This embodiment relates to a method for preparing a current collector having a functional coating, comprising the following steps:

[0091] Step 1: Add the conductive agent Ketjen black, the first binder polyvinylidene fluoride (PVDF) and pure water into a mixer in a mass ratio of 15:7:78, mix for 80 min, and stir at a linear speed of 15 m / s to obtain a first mixed slurry;

[0092] Step 2: adding the second binder polyacrylonitrile (PAN) to the first mixed slurry at a weight ratio of 50 wt% of the weight of the first binder, and continuing to mix using a mixer for 80 min at a stirring blade linear speed of 14 m / s to obtain a second mixed slurry;

[0093] Step 3: adding a metal chelating agent ethylenediaminetetraacetic acid (EDTA) to the second mixed slurry at 8 wt% of the total amount of all binders (the first binder and the second binder), and continuing to mix using a mixer for 80 min at a stirring paddle linear speed of 14 m / s to obtain a third mixed slurry;

[0094] Step 4: adjusting the slurry viscosity of the third mixed slurry to 600 Pa·s to obtain a functional coating slurry;

[0095] Step 5: Use a gravure coater to apply the functional coating slurry to the A and B surfaces of the metal current collector, and pass the coated metal current collector foil through a corona device. After the corona is completed, it is immediately coated and enters the oven. Use a gravure roll with a mesh of 50 honeycomb hexagons, a coating speed of 10 m / min, and a drying temperature of 150°C; roll up to obtain a base-coated foil for lithium batteries or supercapacitor electrodes;

[0096] Step 6: The dry supercapacitor film is composited on both sides of the primer foil by high-temperature roller pressing to prepare a capacitor electrode. The composite temperature is 150°C and the composite speed is 10m / min. Then, it is assembled with a diaphragm (NKK TF 4030) and an electrolyte (DLC 3702) into a 3000F supercapacitor monomer as implementation example 4 and tested.

[0097] Test example

[0098] (1) Adhesion ability test:

[0099] Use 3M tape to bond the current collector to the functional coating, then use a 1 kg roller to roll it repeatedly for 3 times, tear off the tape and check whether it leaks out of the metal current collector surface.

[0100] (2) Supercapacitor internal pressure:

[0101] The internal pressure test sensor is used for internal pressure test. After the capacitor is filled with liquid, the pressure sensor is installed at the injection hole. After installation, the injection hole and the sensor connection are sealed with plasticine and glue to prevent gas leakage. The capacitor floating charge process is as follows: first place the capacitor in a 65℃ oven, let it stand for more than 6 hours, then charge it to 2.7V with a constant current of 100A, keep the voltage at 2.7V, and check the internal pressure value in real time.

[0102] (3) Impedance:

[0103] Use a four-probe test system to test the electrode resistance. First, cut the current collector into a 3*3cm square, place this current collector in the middle of the resistance tester probe, set the test conditions: load tends to -150N, speed 50N / s, error range 1.0N, and read the value after standing for 15s when the load value is reached.

[0104] (4) Cycle performance:

[0105] The cycle test conditions are as follows:

[0106] Place the capacitor in a 65℃ oven and let it stand for at least 6 hours. After the temperature stabilizes, start the test. The process is as follows:

[0107] a) 100A constant current charging to 3.0V;

[0108] b) Let stand for 10 seconds;

[0109] c) 100A constant current discharge to 1.5V;

[0110] d) Let stand for 10 seconds;

[0111] e) Repeat steps a to d.

[0112] from Figure 1 It can be seen that the bonding ability of the primer foil was tested using 3M tape, and the functional coating of the surface-modified metal foil did not expose the substrate ( Figure 1 (a and b), which shows that the adhesion between the current collector and the functional coating is significantly enhanced after surface treatment.

[0113] from Figure 2 It can be seen that the trend of increasing internal pressure of the supercapacitor using the method of the present invention is significantly reduced, indicating that the gas production of the capacitor side reaction is significantly reduced. This shows that the low-cost and high-performance functional coated metal foil current collector (Examples 3 and 4) of the method of the present invention has good interface contact strength, which can significantly improve the electrochemical performance of the energy storage device.

[0114] from Figure 3It can be seen that the conductivity of the conductive coating with a grid dot-shaped protrusion structure (Example 4) is about 35.5% higher than that of the ordinary coating (Example 1), and about 26.4% higher than that of the smooth structure (Example 2), indicating that the structure can effectively improve the interface adhesion and reduce the impedance.

[0115] from Figure 4 It can be seen that the unimproved pole piece (Example 1) cycles at high temperature for 5,000 times, the capacitor explodes, and the capacity decays rapidly; the pole piece with a smooth conductive coating structure (Example 2) cycles to 30,000 times, and the capacity retention rate is 76.7%; the pole piece with a slanted conductive coating structure (Example 3) cycles to 30,000 times, and the capacity retention rate is 83.6%; the pole piece with a grid point-shaped protruding conductive coating structure (Example 4) cycles to 30,000 times, and the capacity retention rate is 91.1%. This shows that the present invention can effectively improve the service life and capacity retention rate of energy storage devices.

[0116] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a current collector having a functional coating, characterized in that: The steps include: (1) uniformly mixing the conductive agent, the first binder and pure water for the first time to obtain a first mixed slurry; Adding a second binder to the first mixed slurry, mixing for a second time to obtain a second mixed slurry; adjusting the slurry viscosity of the second mixed slurry to less than 1000 Pa·s to obtain a functional coating slurry; (2) applying the functional coating slurry to at least one side of a corona-treated metal current collector, and drying the metal current collector to obtain a current collector having a functional coating; The weight ratio of the conductive agent, the first binder and the pure water is 2:1:97-20:10:70; The second binder accounts for 30% to 70% of the weight of the first binder; The parameters for the first mixing in step (1) are: a stirring blade linear speed of 4 m / s to 15 m / s, and a mixing time of 30 min to 120 min; The parameters for the second mixing in step (1) are: the linear speed of the stirring blade is 4 m / s to 15 m / s, and the mixing time is 30 min to 120 min; The first binder includes at least one of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, and styrene-butadiene rubber latex; The second binder includes at least one of acetamide-based binders, starch, polyacrylonitrile, polyacrylate, and polyacrylic acid.

2. The method for preparing a current collector having a functional coating according to claim 1, characterized in that: The conductive agent includes at least one of metal powder, acetylene black, Ketjen black, furnace black, conductive carbon black, conductive graphite, carbon nanotubes, carbon fibers, and graphene.

3. The method for preparing a current collector having a functional coating according to claim 1, characterized in that: Step (1) further includes: adding a metal chelating agent to the second mixed slurry, mixing it for a third time to obtain a third mixed slurry; and adjusting the slurry viscosity of the third mixed slurry to less than 1000 Pa·s to obtain a functional coating slurry.

4. The method for preparing a current collector with a functional coating according to claim 3, characterized in that: The metal chelating agent includes at least one of sodium carbonate, sodium orthophosphate, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetic acid, tetrasodium ethylenediaminetetraacetic acid, disodium nitrilotriacetate, citric acid, tartaric acid and gluconic acid; The metal chelating agent accounts for 2% to 10% of the total weight of the first binder and the second binder; The parameters for the third mixing are: stirring paddle linear speed 4m / s~15m / s, mixing time 30min~120min.

5. A method for preparing a current collector with a functional coating according to any one of claims 1 to 4, characterized in that: The coating method of the functional coating slurry in step (2) includes gravure coating; the shape of the gravure roller surface used in the gravure coating includes at least one of a slash straight line, a diamond quadrilateral, a square, and a honeycomb hexagon; the parameters of the gravure coating are: the mesh number of the gravure roller is 50-300 meshes, the coating speed is 4m / min-60m / min, and the coating thickness is 1μm-12μm; The drying parameters in step (2) are: drying temperature is 50°C to 180°C, and the drying time is 0.5min to 10min.

6. A method for preparing a current collector with a functional coating according to any one of claims 1 to 4, characterized in that: The specific parameters of the corona treatment of the metal current collector in step (2) are: voltage 380V, corona power 2kw~8kw, current 6A~15A, and corona speed 4m / min~60m / min.

7. A current collector having a functional coating, characterized in that: The current collector with a functional coating is prepared by the preparation method according to any one of claims 1 to 6.

8. An application of a current collector having a functional coating, characterized in that: The current collector with a functional coating as claimed in claim 7 is used to prepare an energy storage device.

9. The use of a current collector with a functional coating according to claim 8, characterized in that: The energy storage device includes a lithium-ion battery or a supercapacitor.

Citation Information

Patent Citations

  • Current collector and manufacturing method thereof

    CN110676463A

  • Conductive carbon slurry, positive electrode slurry, and preparation method and application of conductive carbon slurry and positive electrode slurry

    CN114914402A